A STUDY OF ENTREPRENEURIAL MARKETING IN SMALL AND MEDIUM ENTERPRISES (SMEâ€™s) AT UD. KAMANG WANGKO IN LEILEM - Sengkey, Windrista .; Massie, James D.D; Tumewu, Ferdinand . (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract: In Indonesia, SMEs have historically been the main player in domestic economic activities, especially as a large provider of employment opportunities, and hence a generator of primary or secondary sources of income for many household. The purpose of this study is to know the various Entrepreneurial Marketing that applicable for wooden craft and to identify the critical success factor of wooden craft industry. This research is use qualitative type of research, interview method to explore the entrepreneurial marketing of small and medium enterprise in Leilem wooden craft. The population of this research is all elements that can be respondent about the entrepreneurial marketing of small and medium enterprise in Leilem wooden craft. Based on the results of the analysis it was found that Entrepreneurial Marketing in SMEs can increase revenue, selling, building a good communication with the buyers who increase the number of the products wooden craft in Leilem. The result from this research for the company or entrepreneurs and upcoming a new entrepreneurs that interested in opening a new business of wooden craft, it is crucial for the owner to understand about the importance of entrepreneurial marketing.Â Keywords : entrepreneurial marketing, smes, wooden craftÂ